Effects of Filler Content and Coating on the Water and Oil-Based Ink Interactions with a Paper Surface - AYDEMİR, CEM (TAYLOR & FRANCIS AS, 2010)
The effects of filler and coating on the behaviors of water and oil-based ink on the paper surface were investigated. Fillers reduced the air permeability and surface energy hence increased the liquids uptake. The coating was more effective than the internal addition of fillers for the improvement of water and ink absorption. Sizing interfered with the fillers, but had negligible effects on the movements of oil-based ink on papers. The quality of coating in terms of printing performance was dependent on the improvement of surface smoothness, microcapillary formation and the absorption properties of fillers in the coating layer.
Keywords: coating; IGT test; paper filler; paper roughness; print density; sessile drop; sizing; ALKYL KETENE DIMER; LIQUID PENETRATION; DROPLET; HYDROLYSIS; PRESSURE; KINETICS